Evaluatıon Of The Relatıonshıp Between The Transversal Dırectıon And Head Types - T. Ufuk Toygar (Galenos Yayinevi, 2003)
In our study, we aimed to evaluate the relationship between cephalic index and transversal dimension of the head. The sample consisted posteroanterior cephalometric (PA) radiographs and casts of 24 Hiperbarchycephal, 34 Brachycephal, 29 Mesocephal and 24 Dolichocephal patients. The mean chronological age of 114 patients (62 fermale, 52 male) included in the study was 24 years. The patients had no missing teeth and not undergone any orthodontic therapy. Transversal morphology of four head types were assessed with 3 parameters using 2 reference planes from the PA films. Four cast measurements were also assessed in the study. Correlation analysis was carried out on four groups defined according to head types between cephalic index, PA and model parameters, besides ANOVA and Duncan test. Biparietal and bimaxillary distances were significantly different among the head type groups (p<0.01). bimandibular distance was also significant (p<0.05). No statistical differences were observed for model measurements except maxillary intercanine width (p<0.01). Biparietal distance was correlated with cephalic index according to correlation analysis (p<0.01). Bimaxillary distance was negatively correlated with cephalic index (p<0.05). The findings of this study showed that head types were not remarkably associated with transversal dimension of head and face. Genetic control was more effective among the head types. Transversal dimension of the face would likely be much more influenced by enviroment and neuromusculer structures.